The new ceRNA crosstalk between mRNAs and miRNAs in intervertebral disc degeneration - Li, Xingye; An, Yan; Wang, Qilong; Han, Xiao (Frontiers in Cell and Developmental Biology, 2022)
Degeneration of intervertebral disc has been linked to low back pain. To date, pathophysiological mechanisms of intervertebral disc degeneration (IDD) remain unclear, it is meaningful to find effective diagnostic biomarkers and new therapeutic strategies for IDD. This study aimed to reveal the molecular mechanism of IDD pathogenesis from the multidimensional transcriptomics perspective. Here, we acquired IDD bulk omics datasets (GSE67567 and GSE167199) including mRNA, microRNA expression profiles and single-cell RNA sequencing (GSE199866) from the public Gene Expression Omnibus (GEO) database. Through principal component analysis and Venn analysis, we found the different expression pattern in IDD transcription level and identified 156 common DEGs in both bulk datasets. GO and KEGG function analysis showed these dysregulators were mostly enriched in collagen-containing extracellular matrix, cartilage development, chondrocyte differentiation and immune response pathways. We also constructed a potentially dysregulated competing endogenous RNA (ceRNA) network between mRNAs and miRNAs related to IDD based on microRNA target information and co-expression analysis of RNA profiles and identified 36 ceRNA axes including ZFP36/miR-155-5p/FOS, BTG2/hsa-miR-185-5p/SOCS3 and COL9A2/hsa-miR-664a-5p/ IBA57. Finally, in integrating bulk and single-cell transcriptome data analysis, a total of three maker genes, COL2A1, PAX1, ZFP36L2, were identified. In conclusion, the key genes and the new ceRNA crosstalk we identified in intervertebral disc degeneration and may provide new targets for the treatment of IDD.